The effect of disease modifying therapies on fatigue in multiple sclerosis - Cruz Rivera, Samantha; Aiyegbusi, Olalekan Lee; Piani Meier, Daniela; Dunne, Achille; Harlow, Danielle E; Henke, Christian; Kamudoni, Paul; Calvert, Melanie J (Multiple sclerosis and related disorders, 2023)
•Fatigue is a symptom with a serious impact on patients’ quality of life.•Inclusion of fatigue as an RCT outcome is crucial to understand the impact of DMTs.•Limited RCTs of DMTs assessed fatigue as an outcome.•The reporting of PROs of DMT trials assessing fatigue is suboptimal.•Carefully consideration should be given when interpreting the effect of DMTs on fatigue. Fatigue is one of the most common and debilitating symptoms in people with multiple sclerosis (PwMS). Disease-modifying therapies (DMTs) are currently the gold standard in the treatment of MS and their effectiveness has been assessed through randomized clinical trials (RCTs). However, there is limited evidence on the impact of DMTs on fatigue in (PwMS). We conducted a systematic review to 1) understand whether fatigue is included as an outcome in MS trials of DMTs; 2) determine the effects on fatigue of treating MS with DMTs and 3) assess the quality of MS trials including fatigue as an outcome. Two independent researchers systematically searched MEDLINE, EMBASE and ClinicalTrials.gov from 1993 to January 2023 for RCTs that measured fatigue as an outcome. Adherence to reporting standards was assessed with the Consolidated Standards of Reporting Trials (CONSORT)-Patient-Reported Outcomes (PRO), while the risk of bias (RoB) was assessed with the RoB 2 tool by the Cochrane Handbook for Systematic Reviews of Interventions. The systematic review protocol was registered in PROSPERO (CRD42022383321). The search strategy identified 130 RCTs of DMTs of which 7 (5%) assessed fatigue as an outcome. Of the 7 trials, only two presented statistically significant results. In addition, the reporting of fatigue among RCTs was suboptimal with a mean adherence to the CONSORT-PRO Statement of 36% across all trials. Of the 7 trials included, four were assessed as ‘high’ RoB.. Fatigue has a major impact on PwMS yet there is limited trial-based evidence on the impact of DMTs on fatigue. Assessment of fatigue as an outcome is underrepresented in trials of DMTs and the reporting of PRO trial data is suboptimal. Thus, it is imperative that MS researchers conduct RCTs that include fatigue as an outcome, to support clinicians and people with MS (PwMS) to consider the impact of the different DMTs on fatigue.